Properties of Bio-Silver Nanoparticles Mediated by Tuber and Leaf Extracts of Manihot esculenta - Synodalia C. Wattimena; Desy A. Ayuningrum; Leonita Y. Latuasan; Efraim Samson; Philipus J. Patty (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Bio-silver nanoparticle using plant extract has been the subject of many studies nowadays. Researchers use various plant extracts, especially the popular plant from their places. This study aims to synthesize AgNPs using leaf and tuber extracts of M. esculenta Crantz and to characterize their properties to be compared one to another. The characterization includes surface plasmon resonance wavelength using UV-VIS spectroscopy, the chemical bonds related to the extract on the surface of the particles using FTIR spectroscopy, shape and size of the particles using TEM, and antibacterial properties using the disc diffusion method. Each tuber and leaf extract AgNPs were formed a few minutes after mixing silver nitrate with each extract indicated by the change of the color from transparent to yellowish-brown. The color of the sample was quantified by the wavelength of surface plasmon resonance which was found to be 425 nm for tuber extract AgNPs and 430 nm for leaf extract AgNPs. The results of FTIR spectroscopy indicate the presence of the extract at the surface of nanoparticles for both samples. The particles are mostly spherical, but the diameters of the leaf extract AgNPs are relatively smaller than those of the tuber extract AgNPs. The results of antibacterial assays of both samples show that both AgNPs inhibit the growth of S. aureus as effectively as they inhibit the growth of E. coli.